2019
DOI: 10.4103/ijpvm.ijpvm_184_19
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia and health hazards: Smartphone use and addiction among university students

Abstract: Background:Nomophobia, a state of socio-psychological illness, refers to a fear of lack of access to mobile phone, which is thought to be a modern age disorder that causes negative health risks and harmful psychological effects. This study aimed to determine the relationship between the smartphone use and nomophobia disorder among university students.Methods:The study utilized a cross-sectional method in which 320 students were selected via cluster sampling. Data collection tools included a nomophobia and smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 22 publications
4
14
1
6
Order By: Relevance
“…Our results demonstrate that symptoms of nomophobia are associated with symptoms of insomnia. This is consistent with several studies, which demonstrated a strong association between nomophobia and sleep problems (mainly insomnia) [ 3 , 27 , 28 , 29 , 30 , 48 , 49 ]. A direct relationship was found between the nomophobia score of medical students and sleep quality, measured by the Pittsburgh sleep quality index (PSQI) [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrate that symptoms of nomophobia are associated with symptoms of insomnia. This is consistent with several studies, which demonstrated a strong association between nomophobia and sleep problems (mainly insomnia) [ 3 , 27 , 28 , 29 , 30 , 48 , 49 ]. A direct relationship was found between the nomophobia score of medical students and sleep quality, measured by the Pittsburgh sleep quality index (PSQI) [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between nomophobia and sleep problems is better described. A recent systematic review of the nomophobia literature revealed that several studies demonstrated a strong association between nomophobia and sleep problems [ 3 , 27 , 28 , 29 , 30 ]. However, age and sex differences in the association between nomophobia and sleep problems were left unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies 11 , 17 have reported that female participants have a higher prevalence of mobile phone dependence than males. In contrast, a study in Iran 25 found the prevalence of mobile phone dependence to be more in males. Bianchi and Phillips 4 suggested that females use mobile for social reasons while males for technology and work.…”
Section: Discussionmentioning
confidence: 76%
“…This is similar to the findings reported by some previous studies. 14 , 18 , 20 In contrast, study by AzraDaei et al 25 and Mayakal et al 19 found that age was significantly associated with mobile phone dependence. It should be noted, however, participants in the study were aged between 17 and 25.…”
Section: Discussionmentioning
confidence: 94%
“…Research also has linked nomophobia to other mental health disorders such as obsessive behaviors (Daei, Ashrafi-rizi, & Soleymani, 2019;. One study found that excessive cellphone use was associated with obsessivecompulsive behavior and a host of mental health problems such as somatization, interpersonal sensitivity, depression, anxiety, phobic anxiety, hostility, paranoia, and psychoticism (Fırat et al, 2018; see also Gonçalves et al, 2020).…”
Section: Anxiety As An Endogenous Interruptionmentioning
confidence: 99%